2018
DOI: 10.3389/fpsyt.2018.00142
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index in Mild Cognitive Impairment According to Age, Sex, Cognitive Intervention, and Hypertension and Risk of Progression to Alzheimer's Disease

Abstract: Introduction: Mild cognitive impairment (MCI) is a prodromal stage of dementia. The association of body mass index (BMI) and progression to Alzheimer's disease (AD) in MCI subjects according to age, sex, and cognitive intervention remains unknown. We investigated the relationship between BMI and the risk of progression to AD in subjects with MCI, as well as the effect of BMI on progression to AD depending on age, sex, cognitive intervention, and chronic diseases.Methods: Three hundred and eighty-eight MCI subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 37 publications
5
29
1
Order By: Relevance
“…Another study showed that participants with a baseline BMI ≥ 25 kg/m 2 had significantly higher MMSE scores compared with participants with BMI < 25 kg/m 2 (Coin et al, 2012). In mild cognitive impair- (Joo et al, 2018). Moreover, Qizilbash N1 conducted a study in the UK and showed that underweight people had a higher risk of dementia, and the incidence of dementia continued to decrease when BMI increased (Qizilbash et al, 2015), which is consistent with our study.…”
Section: Ta B L E 3 Relevance Between 3-month Mmse Scores and Baselinsupporting
confidence: 89%
See 1 more Smart Citation
“…Another study showed that participants with a baseline BMI ≥ 25 kg/m 2 had significantly higher MMSE scores compared with participants with BMI < 25 kg/m 2 (Coin et al, 2012). In mild cognitive impair- (Joo et al, 2018). Moreover, Qizilbash N1 conducted a study in the UK and showed that underweight people had a higher risk of dementia, and the incidence of dementia continued to decrease when BMI increased (Qizilbash et al, 2015), which is consistent with our study.…”
Section: Ta B L E 3 Relevance Between 3-month Mmse Scores and Baselinsupporting
confidence: 89%
“…It has been shown that long-term intake of high-fat diets, even in the absence of obesity, leads to cognitive deficits (Cifre, Palou, & Oliver, 2018). (Joo et al, 2018). (Joo et al, 2018).…”
Section: Tions Can Inhibit Both Aβ Deposition and Tau Hyperphosphorylmentioning
confidence: 99%
“…The underlying mechanism linking BMI and cognition is not fully understood and requires further research, however some studies have shown that higher BMI in elderly patients is associated with a lower risk of cognitive impairment and dementia [ 51 ], as well as longer survival [ 32 ]. In the latest prospective study, low baseline BMI might be a useful marker for identifying individuals at increased risk for Alzheimer’s Disease in the Mild Cognitive Impairment subjects [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a population of more than three hundred thousand olderly individuals, Qizilbash and colleagues found a lower risk of dementia in people who are overweight and obese, after adjustment for nine potential confounders: age, sex, smoking, alcohol, history of myocardial infraction, stroke and diabetes, use of recent anti-hypertensive drugs, and statins [35]. In other studies adjusted for several important potential confounders, researchers also reported that obesity at baseline predicted a lower risk of AD in elderly people [20,36,37]. Additionally, the results from our study confirmed a higher late-life BMI was associated with lower AD-related biological biomarkers in prodromal AD, larger brain volumes of AD-vulnerable regions and better cognitive performance.…”
Section: Agingmentioning
confidence: 99%